2018
DOI: 10.1007/s00270-018-1999-8
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Reported Outcomes of Bleomycin Sclerotherapy for Low-Flow Vascular Malformations and Predictors of Improvement

Abstract: PurposeThere is paucity of data on patient-perceived outcomes of bleomycin sclerotherapy for low-flow vascular malformations. In this study, the long-term outcomes of bleomycin sclerotherapy were investigated in terms of quality of life (QoL) and patient-perceived changes in health.Materials and MethodsA cohort of Dutch patients with vascular malformations treated with bleomycin sclerotherapy (June 2010-November 2015) completed a questionnaire evaluating disease symptoms, QoL (Short Form 36), patient-perceived… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 28 publications
1
13
0
Order By: Relevance
“…On the other hand, majority of patients were willing to have further treatment. 14 Our results are in close concordance to their material, whether treating intra- or extramuscular VMs. It is easy to agree with their reasoning that often the patient’s expectations exceed the outcome that can realistically be expected leading to only moderate patient satisfaction scores.…”
Section: Discussionsupporting
confidence: 90%
“…On the other hand, majority of patients were willing to have further treatment. 14 Our results are in close concordance to their material, whether treating intra- or extramuscular VMs. It is easy to agree with their reasoning that often the patient’s expectations exceed the outcome that can realistically be expected leading to only moderate patient satisfaction scores.…”
Section: Discussionsupporting
confidence: 90%
“…Thus, only 37% of our patients reported a marked improvement in overall satisfaction. In contrast, in a study where the physicians evaluated the improvement, they found an excellent overall response for 87% of VMs and 84% of LMs [ 16 ]. This discrepancy underlines the importance of collecting patient-reported outcomes.…”
Section: Discussionmentioning
confidence: 98%
“…Considering the patient's age, a radiologist performed ultrasonographyguided needling, and an anesthesiologist performed sclerotherapy using bleomycin under general anesthesia. Bleomycin is reportedly a safe drug in sclerotherapy, with short-term effects, a good degree of patient satisfaction, and no long-term side effects [10,11]. There was a notable improvement in the lesion following sclerotherapy, and had significantly reduced in size on the follow-up imaging outcomes.…”
Section: Discussionmentioning
confidence: 95%